Somatosensory mismatch response in young and elderly adults - Strömmer, Juho M.; Tarkka, Ina M.; Astikainen, Piia (Frontiers in Aging Neuroscience, 2014)
Aging is associated with cognitive decline and alterations in early perceptual processes. Studies in the auditory and visual modalities have shown that the mismatch negativity (or the mismatch response, MMR), an event-related potential (ERP) elicited by a deviant stimulus in a background of homogenous events, diminishes with aging and cognitive decline. However, the effects of aging on the somatosensory MMR are not known. In the current study, we recorded ERPs to electrical pulses to different fingers of the left hand in a passive oddball experiment in young (22–36 years) and elderly (66–95 years) adults engaged in a visual task. The MMR was found to deviants as compared to standards at two latency ranges: 180–220 ms and 250–290 ms post-stimulus onset. At 180–220 ms, within the young, the MMR was found at medial electrode sites, whereas aged did not show any amplitude difference between the stimulus types at the same latency range. At 250–290 ms, the MMR was evident with attenuated amplitude and narrowed scalp distribution among aged (Fz) compared to young (fronto-centrally and lateral parietal sites). Hence, the results reveal that the somatosensory change detection mechanism is altered in aging. The somatosensory MMR can be used as a reliable measure of age-related changes in sensory-cognitive functions.